Ett skydd för testators vilja eller ökade möjligheter för testamentariskt sabotage? - En undersökning av utvalda förslag i SOU 2025:91 - Frieman,Ella (2026)
Wills run the risk of being sabotaged in different ways. To minimize the risk, there is several protection rules in the Swedish law, but they are of an older nature. Our rules about succession are based on the Inheritance Code from 1958, but after many years there has been a suggestion for an update. SOU 2025:91 has been developed to modernize the regulations and adapt them to the new conditions that exist. Some of the suggestions are the in-troduction of a voluntary registry of wills managed by public administra-tion, the possibility of writing a will digitally, a recommendation for more information about witnesses and widened possibilities for emergency wills. The purpose of this essay is to examine these new suggestions and see how they relate to the established law. An account of the historical background is also given. The essay focuses on the testator’s will as the ultimate pro-tective interest and the two sides of the interest. On one hand, no one should be able to sabotage the will which leads to testator’s will not being followed, on the other hand, the testator should be able to freely change and revoke the will. The basis for this presentation of the essay is the legal dogmatic method. The investigation shows how the testator’s will has emerged as a protective interest and its significance for current law. Prenuptial agreements and future powers of attorney are also explained and later compared with the investigation. The essay concludes that some parallels can be drawn to some extent from other regulations. The investigation’s proposal for changes in testamentary law has included the consideration of will-related sabotage. The essay’s analysis discusses how the investigation’s proposal has affected the testator’s will and the two sides of this protective interest. I conclude that the testator’s freedom to change and revoke the will has weighed heavily on the scales. In relation to current law and the view of the testator’s will that has emerged in the investigative part of the essay, I maintain that the investigation’s proposal does not sufficiently protect the testator against will-related sabotage.
Keywords: familjerätt; testamente; arvsrätt; testamentsrätt